2020
DOI: 10.1111/pedi.13099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of youth goal setting in the self‐management of type 1 diabetes and associations with HbA1c: The Flexible Lifestyle Empowering Change trial

Abstract: Introduction: Youth with type 1 diabetes (T1D) commonly do not meet HbA1c targets. Youth-directed goal setting as a strategy to improve HbA1c has not been well characterized and associations between specific goal focus areas and glycemic control remain unexplored. Objective: To inform future trials, this analysis characterized intended focus areas of youth self-directed goals and examined associations with change in HbA1c over a 18 months. Methods: We inductively coded counseling session data from youth in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Eighty percent CGM use equates to 5.5 days of CGM use each week, or approximately 24 days of CGM use each month. Intervention research has shown that setting goals for CGM use may help to increase success 26 . Many youth become frustrated with CGMs after a while and perceive that CGMs interfere with their lives, 27 therefore, setting goals that build in scheduled breaks in CGM use (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty percent CGM use equates to 5.5 days of CGM use each week, or approximately 24 days of CGM use each month. Intervention research has shown that setting goals for CGM use may help to increase success 26 . Many youth become frustrated with CGMs after a while and perceive that CGMs interfere with their lives, 27 therefore, setting goals that build in scheduled breaks in CGM use (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many youth become frustrated with CGMs after a while and perceive that CGMs interfere with their lives, 27 therefore, setting goals that build in scheduled breaks in CGM use (e.g. wearing a CGM for 6 days, with a 1‐day break in CGM use each week) may help to prevent CGM burnout and increase the likelihood of sustaining 80% CGM use across time 26,27 ; however, research is needed to confirm if scheduled breaks in use are an effective strategy to increase CGM use.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to prospectively identify factors that predict individual daily variations in AYA's success in reaching their diabetes goals. Goal setting is a well‐known behavioural strategy to improve DSM 12,25 . Two of the 7 items of the Engagement Prediction Survey predicting daily DSM aligned with the concept of motivation, which was also identified as the strongest predictor of daily self‐management behaviour in prior research with a different population 10 .…”
Section: Discussionmentioning
confidence: 93%
“…Additional strategies include encouraging families to focus on aspects of disease management that are within their control by developing specific and attainable behavioral goals (e.g., daily medication reminders and attending follow‐up appointments). By emphasizing behavioral successes, providers can support patients and families in feeling accomplished with their participation in disease management, thereby reducing distress and impairment 9 …”
Section: Strategies For Addressing Wellbeing and Adherencementioning
confidence: 99%